2021
DOI: 10.1186/s12935-021-01860-9
|View full text |Cite
|
Sign up to set email alerts
|

The importance of CDC27 in cancer: molecular pathology and clinical aspects

Abstract: Background CDC27 is one of the core components of Anaphase Promoting complex/cyclosome. The main role of this protein is defined at cellular division to control cell cycle transitions. Here we review the molecular aspects that may affect CDC27 regulation from cell cycle and mitosis to cancer pathogenesis and prognosis. Main text It has been suggested that CDC27 may play either like a tumor suppressor gene or oncogene in different neoplasms. Diverge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…The major functional isomers of CDC27 are encoded by 19 exons, and CDC27 has two tetratricopeptide repeat (TPR) domains, five TPR motifs at the N-terminal domain and nine TPR motifs in the C-terminal domain ( 44 ). The protein encoded by CDC27 is a component of APC, which had a TPR sequence of its own that is necessary for interaction with certain proteins ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…The major functional isomers of CDC27 are encoded by 19 exons, and CDC27 has two tetratricopeptide repeat (TPR) domains, five TPR motifs at the N-terminal domain and nine TPR motifs in the C-terminal domain ( 44 ). The protein encoded by CDC27 is a component of APC, which had a TPR sequence of its own that is necessary for interaction with certain proteins ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…CDC27 is one of the main components of the anaphase-promoting complex/cyclosome and overexpression and variations in CDC27 expression may affect the cell cycle, mitosis, cancer pathogenesis and prognosis [ 60 , 61 ]. Thus far, there is no specific targeted therapy for CDC27 .…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Lee and his colleagues reported that HSF1 interacts with CDC20 [ 110 ]. This interaction inhibits the association between CDC20 and CDC27, which is one of the canonical subunits of the APC/C complex and is important for mitotic exit and transition into G 1 phase [ 111 , 112 , 113 ] and suppresses the phosphorylation and ubiquitination activity of the APC/C complex [ 110 ]. Subsequently, they showed that HSF1 is localized to the centromere in mitosis and especially to the spindle poles in metaphase, and that phosphorylated HSF1 undergoes ubiquitin degradation during spindle pole localization [ 114 ].…”
Section: Degradation Of Hsfs During Cell Cyclementioning
confidence: 99%